2006
DOI: 10.1158/0008-5472.can-06-0002
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Misfolded Nuclear Receptor Corepressor Confers Resistance to Unfolded Protein Response–Induced Apoptosis

Abstract: We have recently reported that accumulation of misfolded nuclear hormone receptor corepressor (N-CoR) as insoluble protein aggregates in acute promyelocytic leukemia (APL) cells induces endoplasmic reticulum (ER) stress and activates unfolded protein response (UPR). Although accumulation of misfolded proteins is known to trigger UPR-induced cytotoxic cell death in several neurodegenerative disorders, APL cells are notably resistant to UPR-induced apoptosis. The molecular basis for the paradoxical response of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 42 publications
5
39
0
Order By: Relevance
“…The number of cells at S-phase was not significantly affected. vehicle or curcumin, as well as with AEBSF, a broadspectrum protease inhibitor that abrogated N-CoR cleavage in NB4 cells (4). Extract of curcumin-treated NB4 cells did not cleave Flag-tagged N-CoR protein as efficiently as extract of vehicle-treated NB4 cells.…”
Section: Selective Inhibition Of Growth Of Apl Cells By Curcuminmentioning
confidence: 87%
See 2 more Smart Citations
“…The number of cells at S-phase was not significantly affected. vehicle or curcumin, as well as with AEBSF, a broadspectrum protease inhibitor that abrogated N-CoR cleavage in NB4 cells (4). Extract of curcumin-treated NB4 cells did not cleave Flag-tagged N-CoR protein as efficiently as extract of vehicle-treated NB4 cells.…”
Section: Selective Inhibition Of Growth Of Apl Cells By Curcuminmentioning
confidence: 87%
“…We have previously shown how degradation of misfolded N-CoR protein led to the attenuation of ER stress and protected APL cells from UPR-induced apoptosis (4). On the basis of this finding, we hypothesized that amplification of ER stress due to curcumin-induced accumulation of misfolded N-CoR protein in the ER will eventually resensitize APL cells to UPR-induced apoptosis.…”
Section: Curcumin Activates Upr-induced Apoptosis In Apl Cellsmentioning
confidence: 94%
See 1 more Smart Citation
“…Proteolytic processing of PML-RAR by neutrophil elastase, proteinase 3, and cathepsin G, as well as cleavage of misfolded N-CoR by OGSEP, has been implicated in the pathogenesis of APL (12,29). Expression of some of these APL-specific proteases, such as OSGEP and cathepsin G, are indeed restricted to NB4 cells, as their expression was not detected in the non -APL cell line HL-60 (Supplementary Fig.…”
Section: Inhibition Of N-cor Cleavage By Genistein Is Mediated By Dowmentioning
confidence: 99%
“…We have shown that aberrant association of N-CoR with PML-RAR in the cytosol contributed to the misfolding of N-CoR protein (11,12). Therefore, we investigated whether genistein-induced inhibition of N-CoR misfolding results from a possible inhibition of N-CoR binding to PML-RAR in the cytosol.…”
Section: Genistein Inhibits the Binding Of N-cor To Pml-rar And Abrogmentioning
confidence: 99%